Computational principles of movement neuroscience - Wolpert, Daniel M.; Ghahramani, Zoubin (Nature neuroscience, 2000)
Unifying principles of movement have emerged from the computational study of motor control. We review several of these principles and show how they apply to processes such as motor planning, control, estimation, prediction and learning. Our goal is to demonstrate how specific models emerging from the computational approach provide a theoretical framework for movement neuroscience.